2018
DOI: 10.1039/c5cs00933b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular spin qudits for quantum algorithms

Abstract: Presently, one of the most ambitious technological goals is the development of devices working under the laws of quantum mechanics. One prominent target is the quantum computer, which would allow the processing of information at quantum level for purposes not achievable with even the most powerful computer resources. The large-scale implementation of quantum information would be a game changer for current technology, because it would allow unprecedented parallelised computation and secure encryption based on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
254
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 313 publications
(257 citation statements)
references
References 90 publications
0
254
0
3
Order By: Relevance
“…[30] The 159 TbPc 2 molecule is built up from an atomic core of a metal ion surrounded by a shell of organic material (Figure 3). [30] The 159 TbPc 2 molecule is built up from an atomic core of a metal ion surrounded by a shell of organic material (Figure 3).…”
Section: Molecular Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…[30] The 159 TbPc 2 molecule is built up from an atomic core of a metal ion surrounded by a shell of organic material (Figure 3). [30] The 159 TbPc 2 molecule is built up from an atomic core of a metal ion surrounded by a shell of organic material (Figure 3).…”
Section: Molecular Systemsmentioning
confidence: 99%
“…[34] Magnetic studies showed slow relaxation leading to the observation of hysteresis loops; the tetranuclear cage being an SMM. [30] Copyright 2018, the Royal Society of Chemistry. c) Hysteresis loop showing quantum tunneling (QTM) events associated to the nuclear spins.…”
Section: Molecular Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the reduction of the number of operations that are required for the realization of multi-qubit gates remains a crucial problem.One of possible ways to reduce the number of required operations is to use additional degrees of freedom of quantum systems. This idea has stimulated an extended activity [20,21] in theoretical [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and experimental studies [39][40][41][42][43][44][45][46] of quantum computing models with qudits, which are d-dimensional (d > 2) quantum systems. In particular, qudits can be used for substituting ancillas [30,[37][38][39], which allows the reduction of the required number of interactions between information carriers for the realization of multi-qubit gates.…”
mentioning
confidence: 99%